Carboxymethyl Cellulose (CMC) as a template for laccase-assisted oxidation of aniline - Shim, Euijin (2020)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fbioe.2020. 00438/full#supplementary-material